Musical tables : poems - Collins, Billy (Random House, an imprint and division of Penguin Random House LLC, 2022)
""America's favorite poet" (the Wall Street Journal) has found a new form for his unique poetic style: the small poem. Here Collins writes about his trademark themes of nature, animals, poetry, mortality, absurdity, and love--all in a handful of lines. Neither Haiku nor limmerick, and certainly not a gimmick, the small poem pushes to an extreme poetry's famed power to condense emotional and conceptual content into small spaces. Taken together the more than 125 new poems of Musical Chairs show one of our greatest poets channeling his unique voice into a new phase of his luminous career"--